Reduction And Deletion As Copyeditor’s Decisions In Copyediting Process (Journal of Namibian Studies : History Politics Culture, 2023)
Reduction and deletion in translation have a similarity that is eliminating certain information of the source text. Specifically, reduction just eliminates the partial information whereas deletion means eliminating the whole information. The reduction and deletion as the copyeditor’s decisions in editing the translation draft have not been studied yet. Many translation studies have investigated the translation quality in literary works without examining the text before editing. Meanwhile, it is crucial to compare the translation before the editing process (draft) and the translation after editing to find how the copyeditor’s decisions affect the translation quality. This study discusses the result of an investigation on how reduction and deletion as copyeditor’s decisions affect the translation quality. A translation approach was used in this qualitative research to analyze the quality of the translation from English into Indonesian. Objective data were collected through purposive sampling from Julie Anne Peters’ novel by the Time You Read This I’ll be Dead, its translation draft, and its edited version. This study is done to obtain information on how reduction and deletion affect the translation quality of the edited version as the final work that is published. The results show that the reduction and deletion decisions have negative effects on the translation quality. It was found that the reduction decreased the translation quality, especially the accuracy. Meanwhile, the deletion decreased the translation quality not only on the aspect of accuracy but also acceptability and readability. This implies that the copyeditor should be cautious and avoid the reduction and deletion decisions to maintain the translation quality.